Climate crisis and recent developments in bio-based restoration of ecosystems. (15th April 2023) - Mikulčić, Hrvoje; Wang, Xuebin; Duić, Neven; Dewil, Raf
Abstract: Over the years, due to the climate crisis, sustainable economic growth and biodiversity protection have been increasingly promoted. Scientists, researchers, and experts in the field of sustainable development highlighted that bio-based restoration of ecosystems and responsible management of existing resources are needed to meet the needs of future generations. This paper discusses some of the latest developments in three main areas of sustainability, i.e., energy, water and environment, that emerged from the "16th Sustainable Development of Energy, Water and Environment Systems Conference – SDEWES 2021". The purpose of this introduction article is to briefly review the articles included in this Virtual Special Issue. As such, it acts as an editorial paper for the virtual special issue of the Journal of Environmental Management, dedicated to the SDEWES 2021 conference.